1986
DOI: 10.1007/bf02428050
|View full text |Cite
|
Sign up to set email alerts
|

TheBrassica mitochondrial DNA plasmid and large RNAs are not exclusively associated with cytoplasmic male sterility

Abstract: More than 100 different Brassica nucleo-cytoplasmic combinations were analysed for the presence or absence of the 11.3 kb mitochondrial plasmid. Contrary to some previous reports, no close association exists between the presence of the plasmid and cytoplasmic male sterility. Some novel abundant RNAs which copurified with Brassica mitochondria are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 10 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Brassica has already been demonstrated [46,24]. The disappearance of this 11.3 kb plasmid via in vitro culture was also recently shown by Erickson et al [ 13].…”
Section: Patterns Of Mtdna Change In Independent Culture Linesmentioning
confidence: 77%
See 1 more Smart Citation
“…Brassica has already been demonstrated [46,24]. The disappearance of this 11.3 kb plasmid via in vitro culture was also recently shown by Erickson et al [ 13].…”
Section: Patterns Of Mtdna Change In Independent Culture Linesmentioning
confidence: 77%
“…HMV denotes high molecular weight undigested mtDNA. The arrows denote the array of putative RNA molecules that occasionally co-purify with mtDNA [24].…”
Section: Patterns Of Mtdna Change In Independent Culture Linesmentioning
confidence: 99%
“…These dsRNAs appear to replicate independently of the cellular DNA (Finnegan and Brown 1986); however, their natural infectivity has never been proved and their biological significance is unknown but of considerable interest. Some dsRNAs are correlated with male sterility of the host plants (Grill and Garger 1981;Scalla et al 1981;Sisco et al 1984), although other authors question a causal connection between the dsRNAs and this phenotype (Kemble et al 1986;Mackenzie et al 1988). …”
Section: Introductionmentioning
confidence: 96%
“…However, an extensive analysis using more than 100 different Brassica nucleocytoplasmic combinations later revealed that there was no close association between the presence of this plasmid DNA and the cms trait (Kemble et al 1986). There have been no further reports regarding the biological role of this linear molecule in rapeseed mitochondria to date.…”
Section: Introductionmentioning
confidence: 97%